US Field Hockey (USFHA) (2006)
The United States Field Hockey (USFHA) is the national governing body for Field Hockey in the United States and is a member of the United States Olympic Committee, Federation Internationale de Hockey and the Pan American Hockey Federation. The mission of the USFHA is to: 1. Provide programs and services for our members, supporters, affiliates and the interested public. 2. Be committed to excellence and the improvement of opportunities for both men and women in our sport, emphasizing participation and development opportunities for players, coaches, umpires and administrators. 3. Be committed to selecting and preparing teams to participate successfully in the Olympic Games, Pan American Games and identified international competitions. 4. Strive to represent the United States and the sport of field hockey in an exemplary manner throughout the world, both in terms of competitive performance and in the overall quality of our programs and services to our members.